2003
DOI: 10.1124/mol.64.4.857
|View full text |Cite
|
Sign up to set email alerts
|

A Presynaptic Action of the Neurosteroid Pregnenolone Sulfate on GABAergic Synaptic Transmission

Abstract: The endogenous neurosteroid pregnenolone sulfate (PS) is known to enhance memory and cognitive function at nanomolar concentrations. However, the effect of these low concentrations on synaptic transmission has not been previously studied. The effects of PS on GABA A receptor-mediated inhibitory postsynaptic currents were studied in cultured hippocampal pyramidal neurons. Concentrations of PS similar to those endogenous in the hippocampus (10 -30 nM) reduced the frequency of both action potential-dependent (spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 40 publications
6
51
1
Order By: Relevance
“…This neurosteroid enhancement of mIPSCs from medial preoptic neurons has been confirmed by Uchida et al (2002). Sulfated neuroactive steroids can inhibit GABA release from hippocampal pyramidal cells by acting on a sigma receptor (Mtchedlishvili and Kapur, 2003). While our laboratory has confirmed the ability of a sulfated neurosteroid to inhibit GABA release (unpublished data from Purkinje neurons), our laboratory and others (Cooper et al, 1999;Puia et al, 2003) have not observed a change in frequency of mIPSCs at low concentrations of unsulfated neuroactive steroids from terminals influencing hippocampal or cerebellar Purkinje neurons.…”
Section: Neurosteroid Involvement In the Gabamimetic Profile Of Ethansupporting
confidence: 64%
See 1 more Smart Citation
“…This neurosteroid enhancement of mIPSCs from medial preoptic neurons has been confirmed by Uchida et al (2002). Sulfated neuroactive steroids can inhibit GABA release from hippocampal pyramidal cells by acting on a sigma receptor (Mtchedlishvili and Kapur, 2003). While our laboratory has confirmed the ability of a sulfated neurosteroid to inhibit GABA release (unpublished data from Purkinje neurons), our laboratory and others (Cooper et al, 1999;Puia et al, 2003) have not observed a change in frequency of mIPSCs at low concentrations of unsulfated neuroactive steroids from terminals influencing hippocampal or cerebellar Purkinje neurons.…”
Section: Neurosteroid Involvement In the Gabamimetic Profile Of Ethansupporting
confidence: 64%
“…As with GABA transmission, a number of presynaptic mechanisms can influence glutamate release (see Brown et al, 2004;Jones and Wonnacott, 2004). Since ethanol increases neurosteroids, another aspect that should receive future attention is the possibility that pregnenolone sulfate may enhance spontaneous glutamate release (see Meyer et al, 2002), while reducing release of GABA (Mtchedlishvili and Kapur, 2003). Such an action would likely relate to adaptations induced by chronic ethanol exposure.…”
Section: Ethanol On Excitatory Drivementioning
confidence: 99%
“…Previous studies in chick spinal chord neurons had suggested that PS had a higher potency at GABA A receptors than at NMDA receptors. In the past, we have characterized the PS modulation of GABA A receptors on hippocampal dentate granule cells (Mtchedlishvili et al, 2001) and in cultured hippocampal neurons (Mtchedlishvili and Kapur, 2003) but we have not investigated PS modulation of NMDA currents.…”
Section: Ps Enhancement Of Nmda Receptor Currentsmentioning
confidence: 99%
“…These studies suggest that PS inhibits GABAergic synaptic transmission with greater potency and efficacy than it enhances glutamatergic neurotransmission. PS effects on GABAergic synapses were characterized in detail recently (Mtchedlishvili and Kapur, 2003). PS blocks GABA release in a very potent manner, with an IC 50 of 26 nM, and GABA release is suppressed 80-90% by 1-10 µM PS.…”
Section: Mechanism Of Convulsant Actionmentioning
confidence: 99%
“…PREG-S-is an excitatory neuroactive steroid that inhibits GABA release at nanomolar concentrations (Mtchedlishvili and Kapur, 2003), inhibits GABA A receptors, and potentiates N-methyl-D-aspartate (NMDA) receptor-mediated excitatory responses at micromolar concentrations (Majewska et al, 1988;Wu et al, 1991). PREG-S modulates learning and memory in rodents (Flood et al, 1992;; its concentrations decrease with age and administration of PREG-S reverses cognitive deficits in aged rats (Vallee et al, 2001).…”
Section: Introductionmentioning
confidence: 99%